Performance of Diesel Particulate Filter (DPF) in reducing exhaust gas opacity in diesel engines - Samudra, Agung; Rahmat, Muhammad Hudan; Murwantini, Sri; Suprayogi, Thathit (Universitas Mercu Buana, 2025)
This research aims to determine the performance of the Diesel Particulate Filter (DPF) in reducing exhaust gas opacity, smoke temperature and noise levels on the 1997 Isuzu Panther. The DPF used in this research is made of copper and stainless steel with a metallic honeycomb model. This experimental study involved installing a DPF on a standard diesel vehicle exhaust system and measuring exhaust emissions, smoke temperature and noise levels. The measuring instrument used to test the opacity and temperature of the exhaust gas is a smoke opacity meter based on the SAE-J1667 test procedure (snap acceleration test procedure). Meanwhile, to test the noise level, a sound level meter based on ISO/FDIS 5130:2006 (E) standard was used. Tests were carried out under various conditions including standard exhaust testing (Non-DPF), standard exhaust with DPF (DPF), DPF with 50 gram stainless steel material (DPF + SS50), DPF with 100 gram stainless steel material (DPF + SS100), and DPF made of 150 gram stainless steel (DPF + SS150). The test results showed that DPF had a significant effect on reducing exhaust opacity, smoke temperature and noise level of the 1997 Isuzu Panther. The greatest reduction in exhaust opacity, smoke temperature and noise level were produced by DPF + 150 gram stainless steel with exhaust opacity that could be reduced by 87, 1 ± 1.1%, smoke temperature of 43.2 ± 1.7%, and noise level of 15.2 ± 1.3%. These findings open up opportunities for the development of DPF technology that is more efficient in reducing diesel vehicle emissions, contribute to stricter emissions regulations, and support filter design innovation to improve air quality and reduce the negative impact of vehicles on the environment. In addition, the results of this research show that the use of DPF is in accordance with the diesel vehicle emission threshold regulations set in Indonesia.